Spectroscopy and 3.01 μm laser performance of Ho:YAP oxide crystal pumped by 1150 nm Raman laser. (January 2023) - Qiao, Yang; Sun, Dunlu; Zhang, Huili; Luo, Jianqiao; Quan, Cong; Hu, Lunzhen; Han, Zhiyuan; Dong, Kunpeng; Chen, Yuwei; Cheng, Maojie
Highlights: High-quality Ho:YAP crystal was fabricated by the Czochralski method. The structure, spectroscopy and J-O parameters of Ho:YAP were discussed. For the first time, ∼3 μm CW laser was realized in single Ho-doped crystal host. Maximum power of 176 mW and slope efficiency of 3.36% was obtained. Abstract: We demonstrate the spectroscopy and mid-infrared laser performance on the Ho:YAP oxide crystal grown by the Czochralski method in detail. The crystal belongs to orthorhombic system of Pnmb (62) space group and shows high crystalline quality. The lifetimes of 5 I6 and 5 I7 levels are 0.412 and 4.485 ms, respectively. Particularly, under 1150 nm Raman fiber laser pumping, a 3.01 μm CW laser with a maximum power of 181 mW and slope-efficiency of 3.35% is achieved. The M 2 factor of 1.35/1.37 indicates that the yield laser has excellent beam quality. The results reveal that the Ho:YAP crystal possesses great potential for developing efficient 3.0 μm mid-infrared lasers.